Frustration, aggression, and the non-violent semai - Robarchek, Clayton A. (American Anthropological Association, 1977)
The frustration-aggression hypothesis has provided the dominant paradigm for the psychological study of aggression during the more than three decades since it was first formulated by Dollard and his co-workers. Although the hypothesis has been widely criticized in the intervening years and the original formulation has been subject to numerous revisions and qualifications, the central assertion of a causal relationship between an antecedent frustrating event and the consequent occurrence of an aggressive response remains largely intact. In one or another of several modern formulations the hypothesis continues to inspire a good deal of research and theorizing concerning the nature and sources of human aggression, much of which has significant social and political implications, for example, scapegoat theories of prejudice (Allport 1954) and deprivation theories of social violence (Davies 1962).